Stereocomplex Polylactide for Drug Delivery and Biomedical Applications: A Review - Im, Seung Hyuk; Im, Dam Hyeok; Park, Su Jeong; Chung, Justin Jihong; Jung, Youngmee; Kim, Soo Hyun (MDPI, 2021)
Polylactide (PLA) is among the most common biodegradable polymers, with applications in various fields, such as renewable and biomedical industries. PLA features poly(D-lactic acid) (PDLA) and poly(L-lactic acid) (PLLA) enantiomers, which form stereocomplex crystals through racemic blending. PLA emerged as a promising material owing to its sustainable, eco-friendly, and fully biodegradable properties. Nevertheless, PLA still has a low applicability for drug delivery as a carrier and scaffold. Stereocomplex PLA (sc-PLA) exhibits substantially improved mechanical and physical strength compared to the homopolymer, overcoming these limitations. Recently, numerous studies have reported the use of sc-PLA as a drug carrier through encapsulation of various drugs, proteins, and secondary molecules by various processes including micelle formation, self-assembly, emulsion, and inkjet printing. However, concerns such as low loading capacity, weak stability of hydrophilic contents, and non-sustainable release behavior remain. This review focuses on various strategies to overcome the current challenges of sc-PLA in drug delivery systems and biomedical applications in three critical fields, namely anti-cancer therapy, tissue engineering, and anti-microbial activity. Furthermore, the excellent potential of sc-PLA as a next-generation polymeric material is discussed.
Keywords: ENANTIOMERIC POLY(LACTIC ACID)S; POLYELECTROLYTE COMPLEXES; MECHANICAL-PROPERTIES; COMPRESSIVE STRENGTH; VASCULAR SCAFFOLDS; DEXTRAN HYDROGELS; CROSS-LINKING; TISSUE; ANTIBACTERIAL; PH